Tinjauan Aktivitas Fisik/Olahraga Masyarakat Kota Padang Sidempuan Di Tengah Pandemi Virus Corona (Covid 19) - Zumadi Ashari Nasution; Anton Komaini; Ahmad Chaeroni; Yogi Andria (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The problem in this study is that the physical/sports activities of the people of Padangsidempuan City are not known in the midst of the Corona Virus Pandemic (Covid 19). The purpose of this study was to determine the physical/sports activities carried out by the people of Padangsidempuan City in the midst of the Corona Virus Pandemic (Covid 19). This type of research is descriptive. The population in this study were adolescents aged 14-21 years. Sampling was done by incidental sampling technique. The number of samples taken in this study were 60 teenagers. Where 40 people to fill out the questionnaire and 20 people to interview. The technique used to collect data is interviews and questionnaires or questionnaires. The data were analyzed using the frequency distribution formula in the form of percentages. The results of the study were obtained as follows: Physical activity/sports of the people of Padangsidempuan City in the Middle of the Corona Virus Pandemic (Covid 19) was in the sufficient classification, this was evidenced by the percentage value of the answers of 53.26%. This means that the physical activity/sports of the people of Padangsidempuan City in the midst of the Corona Virus Pandemic (Covid 19) is sufficient to carry out sports activities, but it is not optimal and needs to be increased again.